2015
DOI: 10.1007/s00429-015-1039-2
|View full text |Cite
|
Sign up to set email alerts
|

A central mesencephalic reticular formation projection to the supraoculomotor area in macaque monkeys

Abstract: The central mesencephalic reticular formation is physiologically implicated in oculomotor function and anatomically interwoven with many parts of the oculomotor system’s premotor circuitry. This study in Macaca fascicularis monkeys investigates the pattern of central mesencephalic reticular formation projections to the area in and around the extraocular motor nuclei, with special emphasis on the supraoculomotor area. It also examines the location of the cells responsible for this projection. Injections of biot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 95 publications
(162 reference statements)
5
31
0
Order By: Relevance
“…The collicular projection is also likely to be separate from the projection to EWpg described here, as Moschovakis et al (1988) did not observe non-tectal axon collaterals for cMRF reticulotectal neurons. The projection to EWpg is probably also separate from the population of cMRF neurons sending axons to the medulla and spinal cord, as these reticulospinal and reticuloreticular neurons display a very different distribution within the cMRF (Warren et al 2008; Perkins et al 2009) than those reported to project to the SOA and EWpg (Bohlen et al 2015). Certainly, a connection between lens and pupil control and head turning would not be expected.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The collicular projection is also likely to be separate from the projection to EWpg described here, as Moschovakis et al (1988) did not observe non-tectal axon collaterals for cMRF reticulotectal neurons. The projection to EWpg is probably also separate from the population of cMRF neurons sending axons to the medulla and spinal cord, as these reticulospinal and reticuloreticular neurons display a very different distribution within the cMRF (Warren et al 2008; Perkins et al 2009) than those reported to project to the SOA and EWpg (Bohlen et al 2015). Certainly, a connection between lens and pupil control and head turning would not be expected.…”
Section: Discussionmentioning
confidence: 97%
“…While neither the confocal nor the ultrastructural evidence is incontrovertible, the combined results from these two lines of evidence strongly support the contention that cells in the cMRF synaptically contact preganglionic motoneurons. Previous work has already shown that injections of retrograde tracers that include the EWpg along with the supraoculomotor area (SOA) and oculomotor nucleus (III) do label cells within the cMRF (Bohlen et al 2015). These cells occupy a horizontally oriented sublamina within the middle third of the cMRF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6] These reach the medial longitudinal fasciculus for downgaze and pretectal plate for upgaze. 7 Supranuclear paralysis of upgaze results from bilateral lesions of the pretectal area involving the fibers and nuclei of the posterior commissure. A single lesion of the posterior commissure, as seen in our patient, can at times result in upgaze paralysis due to the large decussation of fibers within the commissure.…”
Section: Oy-stersmentioning
confidence: 99%